OPTIMALISASI KINERJA BADAN PERMUSYAWARATAN DESA (BPD) DALAM PEMBUATAN PRODUK HUKUM DESA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Wibowo, Fahrudin Ari; Maharani, Andina Elok Puri (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
This research aims to find out the Role of Village Consultative Department in Making Village Law Products after the validation of The Villages Act No. 6 of 2014, and the problem in implementing the Role of Village Consultative Department in Making Village Law Products in Makamhaji Village and Pucangan Village, Kartasura, Sukoharjo.This research is descriptive empirical law research. The types of data used are primary data and secondary data. The primary source used is a direct interview with the participant. Secondary data sources are literature, legislation, journals, articles and materials from the internet and other related sources. The data collection technique used is a field study by going directly to the object of research and literature study to obtain a theoretical basis.Based on the results of the research and discussion, it was concluded that the implementation of the Village Consultative Department’s role in making Village Law Products had not been carried out maximally, the staff of the Village Consultative Department were still passive and limited to discussing and approving the draft Village Regulation. The Village Consultative Department in making Village Regulations also experienced various problems.